Psychological help for family members of cancer patients at different stages of the treatment - Mukharovska, I. R. (Journal of Education, Health and Sport, 2017)
The targets for medical and psychological assistance to family members of cancer patients at different stages of treatment are determined in the article presented. Materials and methods. The study was carried out at the Kyiv Municipal Clinical Oncological Center, 218 family members of patients with cancer took part in it. 79 persons had a sick relative at the stage of initial treatment, 68 –re-treatment and 71 –at palliative care. Diagnostic tools –psychodiagnostic semi-structured interviews. Results. Relatives of cancer patients experienced high levels of stress due to diagnosing cancer in their loved one, which manifested in emotional stress, disturbance of family functioning, difficulties interaction with the patient, the formation not adaptive behavior. The content features of the various stages of treatment determined differences in the psychologicaltasks and activities. Conclusions. Psychological measures for family members of cancer patients is important part ofpsychooncological help.